Hyperthermic intrathoracic chemotherapy (HITOC) after cytoreductive surgery for pleural malignancies: a retrospective, multicentre study - Ried, Michael; Kovács, Julia; Markowiak, Till; Müller, Karolina; Huppertz, Gunnar; Koller, Michael T.; Winter, Hauke; Klotz, Laura Valentina; Hatz, Rudolf A.; Zimmermann, Julia; Passlick, Bernward; Schmid, Severin Thomas; et al. (Cancers, 2021)
Abstract: In the context of quality assurance, the objectives were to describe the surgical treatment and postoperative morbidity (particularly renal insufficiency). A retrospective, multicentre study of patients who underwent cytoreductive surgery (CRS) with cisplatin-based HITOC was performed. The study was funded by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation (GZ: RI 2905/3-1)). Patients (n = 350) with malignant pleural mesothelioma (n = 261; 75%) and thymic tumours with pleural spread (n = 58; 17%) or pleural metastases (n = 31; 9%) were analyzed. CRS was accomplished by pleurectomy/decortication (P/D: n = 77; 22%), extended P/D (eP/D: n = 263; 75%) or extrapleural pneumonectomy (EPP: n = 10; 3%). Patients received cisplatin alone (n = 212; 61%) or cisplatin plus doxorubicin (n = 138; 39%). Low-dose cisplatin (≤125 mg/m2 BSA) was given in 67% of patients (n = 234), and high-dose cisplatin (>125 mg/m2 BSA) was given in 33% of patients (n = 116). Postoperative renal insufficiency appeared in 12% of the patients (n = 41), and 1.4% (n = 5) required temporary dialysis. Surgical revision was necessary in 51 patients (15%). In-hospital mortality was 3.7% (n = 13). Patients receiving high-dose cisplatin were 2.7 times more likely to suffer from renal insufficiency than patients receiving low-dose cisplatin (p = 0.006). The risk for postoperative renal failure is dependent on the intrathoracic cisplatin dosage but was within an acceptable range